Sistem Pakar untuk Pertolongan Pertama pada Penyakit Umum menggunakan Metode Forward Chaining - Hartono, Joshua Ricky; Budhi, Gregorius Satia; Dewi, Lily Puspa (Jurnal Infra, 2015)
Application of expert systems are now widely used by many people, as well as application development is quite fast and good. So easy to use and many of the benefits with this application. With this application, common people can learn the science of an expert to be applied into daily life.In this study expert system is applied to diagnose the disease as first aid before consulting a doctor. In making this application, programmers consult the experts (doctors) to create a knowledge-based.Based on the questionnaire results obtained that the expert system application program as a first aid for common ailments can run well and well-presented in user interface.